(untitled) (Journal of Science and Technology, 2016)
This study investigated the use of pattern recognition techniques in intelligent diagnosis of rotating machinery. Existing literature on machine fault diagnosis suggested many approaches to machine diagnosis: notable among them are pattern recognition technique, data mining and Hidden Marken, Modelling. A method using MEP neural network classifier for pattern recognition offault in a centrifugal pumprig has been developed, The study was primarily experimental and involved the simulation of sir types of faults on a centrifugal pump, one at a time. There were bearing failure, seal ring wear, misalignment, unbalance on impeller, cavitation, and unbalance on coupling. Data were collected using a portable data acquisition system: SKF Microlog. Data were collected when the pump was in no-fault condition. Each fault was trained on a separate neural network, giving a total of six opes of networks with different number of inputs and only one output. The results obtained from the simulation work confirmed previous studies that pattern recognition technique is effective in recognising and classifying machine faults. Using the seat-ring wear as an example, the distribution of weight vectors showed low weight values distributed around zero is a sign of a healthy network. The distribution was also slightly skewed to the left, indicating the presence of large weight values, and subsequently, the network may have slightly over-fitted the data. The error associated with a decision made by the network was evaluated. After 240 epochs, an average error of 0.004070 was obtained. The validation set error obtained was 0.0%.